Methylation matters?: decreased methylation status of genomic DNA in the blood of schizophrenic twins - Boensch, Dominikus; Weisbrod, Matthias (Psychiatry research, 2012)
Studies of schizophrenia inheritance in identical twins show a concordance of about 50%, which supports an epigenetic model. In our present study we investigated methylation of genomic DNA and promoter methylation of Reelin and SOX10 genes in peripheral blood of twins suffering from schizophrenia. Global DNA methylation was reduced (52.3%) in schizophrenic twins if compared with healthy control twins (65.7%). The reduced methylation was significant in males only. We also found a similar hypomethylation in the non-affected twins of discordant pairs and a mixed group of psychiatric controls. In discordant twins there was a relative hypermethylation of the SOX10 promoter. Within-pair-difference of methylation of Reelin promoter was significantly lower in monozygotic twins than in dizygotic twins.
Gesehen am 16.10.2018